Management of R&D cooperation - Christian Müller; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 1999)
Because of the high degree of technological complexity and the increasing convergence of new technologies, it is becoming more and more difficult to develop advanced products for those companies who solely rely on their own in-house 'core competencies'. One possible response made to these rising requirements is the consideration of cooperation with other companies. Since prior research on cooperation is extensive in its theoretical scope and diverse in its disciplinary bases, it seems appropriate to give a short overview on the literature. In this article, we pursue two purposes: Firstly, we provide a brief and comprehensive picture of theoretical findings on technology-related cooperation pertinent to practitioners by using a process-oriented framework which helps us to integrate the existing literature from different academic disciplines. Secondly, while management scholars have primarily tended to focus on certain research streams, we draw attention to some issues not sufficiently covered by the literature today. We highlight the importance of the technological content (incremental vs. breakthrough and product vs. process innovations) as well as the orientation of the cooperation (horizontal vs. lateral) which should be considered in more detail in future research.
urn:nbn:de:gbv:830-opus-1660
Keywords: 650